Divided They Fell Crisis and the Collapse of Europe's Centre-Left. - McDaniel, Sean (Building progressive alternatives., 2023)
Examines the failures of mainstream politics, and in particular the inability of the centre-left - the UK Labour Party and France's Parti Socialiste - to respond to the Great Recession more effectively.